The Utility of a Pediatric COVID-19 Online Forward Triage Tool in Switzerland - Michel, Janet; Mettler, Annette; Starvaggi, Carl; Travaglini, Nicola; Aebi, Christoph; Keitel, Kristina; Sauter, Thomas C. (Frontiers in Public Health, 2022)
Background To offset the burden on the health system, hospitals set up telehealth interventions, such as online forward triage tools (OFTT). The website www.coronabambini.ch was developed to specifically address the needs of children and their families in Switzerland and to facilitate the decision to test, isolate, attend school, or access the health care system. Methods Video interviews were held with key informants (n = 20) from a population of parents, teachers, guardians, as well as doctors who had used the child-specific COVID-19 OFTT and had consented to a further study. Convenience and quota sampling were done to include a variety of key informants. Interviews were recorded, transcribed verbatim, and analyzed for themes. Results Three main themes emerged: i) the usefulness of the OFTT to the users, ii) expectation management and importance of stakeholder involvement in OFTT development, and iii) OFTT limitations. Conclusion Our study highlights opportunities, limitations, and lessons to consider when developing a pediatric COVID-19 OFTT. The involvement of stakeholders, parents, teachers, and health care providers in the design, set up, implementation, and evaluation of telehealth interventions is critical as this can help with expectation management and enhance OFTT utility.